Fiscal federalism and electoral accountability - Toke Aidt; Jayasri Dutta (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study the efficient allocation of spending and taxation authority in a federation in which federal politicians are exposed to electoral uncertainty. We show that centralization may, but need not, result in a loss of electoral accountability. We identify an important asymmetry between positive and negative externalities and show that centralization may not be efficient in economies with positive externalities even when regions are identical and centralization does not entail a loss of accountability. We also show that decentralization can only Pareto dominate centralization in economies with negative externalities.
Keywords: D72; D78; H41; 330; fiscal federalism; local public goods; externalities; performance voting; turnout uncertainty; electoral accountability; Finanzföderalismus; Lokales öffentliches Gut; Externer Effekt; Wiederwahl; Theorie